MAQOLLARDA NUTQIY AKT - Yaxyoyeva Umida Ibrohim qizi (TADQIQOTLAR.UZ, 2024)
In this article, speech acts, which played an important role in proverbof linguistic pragmatics and became one of the special fields of anthropocentric theory according to their methodological status, are theoretically studied.